Applying variable dissolved oxygen set point in a two level hierarchical control structure to a wastewater treatment process. (April 2015) - Santín, I.; Pedret, C.; Vilanova, R.
Abstract : Highlights: A hierarchical control structure for biological wastewater treatment plants. MPC with inlet flow rate feedforward control is proposed for the low level. MPC, Affine Function and fuzzy controller are tested for the high level. A tuning region improves simultaneously effluent quality and operational costs. Affine Function and fuzzy control perform better than MPC. Abstract: This paper presents a two-level hierarchical control structure for biological wastewater treatment plants, with the goal of improving effluent quality and reducing operational costs. The Benchmark Simulation Model No. 1 is used as working scenario. The hierarchical structure allows to adjust the dissolved oxygen in the fifth tank (SO, 5 ) according with the working conditions, instead of keeping it in a fixed value. Model Predictive Control (MPC) with inlet flow rate feedforward control (MPC + FF) is proposed for the lower level to control nitrate nitrogen concentration of the second tank and SO, 5 . MPC, Affine Function and fuzzy controller are tested for the higher level to adjust the SO, 5 set point of the lower level based on the ammonium and ammonia nitrogen concentration in the fifth tank. Modifying the tuning parameters of the higher level, a tuning region is determined, in which the effluent quality and operational costs are simultaneously improved.